Dynamic characterization of viscoelastic materials used in composite structures. (December 2014) - Fotsing, ER; Sola, M; Ross, A; Ruiz, Edu
The main focus of this paper is the experimental comparative analysis of the viscoelastic properties of acrylic- and silicon-based viscoelastic materials. These materials are widely used in the aeronautic industry for structural and/or damping applications. It is therefore required to determine their viscoelastic properties such as shear modulus and loss factor following their integration to aircraft composite structures. The influence of material thickness, bonding quality, curing and cocuring with composite material was evaluated using dynamic mechanical analysis machine in plan shear configuration. This comparative analysis in the 0–600 Hz frequency range provides useful information that should be taken into consideration when designing bonded joints for structural and/or damping applications. The small variation of the acrylic-based material loss factor over a wide range of frequencies suggests that this material is a good candidate for damping applications at room temperature in metallic structures where no curing is required. However, cocuring of acrylic-based material with composite laminae increases its shear modulus up to six times with respect to the uncured material whereas its loss factor is reduced by about 20%. On the other hand, the silicon-based material remains stable after thermal treatment (curing and cocuring) suggesting that it is well suited for in situ damping treatment involving laminate composite structure. However, at room temperature its shear modulus after cocuring is lowered by almost 25% due to poor bonding quality, which depends on the nature of the substrate.